Ecologia reprodutiva do peixe donzela, Stegastes sanctipauli Lubbock & Edwards, 1981 (Osteichthyes: Pomacentridae) no arquipélago de São Pedro e São Paulo, Brasil - Alves, Aline Cristina (2013)
Damselfishes play key roles in reef environments and are widely used as models in ecological and behavioral studies.During the reproductive period, the damselfishes present strategies involving benthonic spawning. The parental care is performed by the male who, during the days of egg development, expelled all potential predators that try to attack their territory. It was studied here the behavioral ecology during spawning period and the reproductive success of Stegastes sanctipauli, a damselfish endemic to the remote St. Peter and St. Paul s Archipelago (Mid Atlantic Ridge, Brazil). Nest abundance was negatively influenced by depth and abundance of Caranx lugubris, an important damselfish predator. The number of clutches within male s nests was positively influenced by depth, nest area, and substrate inclination, with deeper, bigger and more inclined nests sheltering more clutches. Number of clutches within nests varied along the lunar cycle, peaking at two days before the new moon. Egg loss per clutch per day ranged from 3.5% to 50% and was positively influenced by the initial number of eggs laid by females and moon phase, with highest losses recorded also in the days before the new moon. Frequency of agonistic interactions increased with nest size. Bigger nests, that shelter more clutches, are possibly more attractive to potential egg predators. Species most frequently recorded attempting to predate S. sanctipauli eggs were the conspecifics, heterospecifics damselfishes (Chromis multillineata and Abudefduf saxatilis), Malacoctenus sp. and Halichoeres radiatus. Although, no successful predation events was witnessed, experimental offer of clutches and analysis of bite scars revealed Melichthys niger as the main potential predator of S. sanctipauli eggs. Filial cannibalism of eggs was frequently observed, and may be pointed as a major cause of S. sanctipauli embryo mortality.